A Storm of Swords: A Song of Ice and Fire #3 - Martin, George R. R. (New York : Bantam Books, 2011)
The three surviving contenders for the throne of the Seven Kingdoms continue to struggle among themselves, Robb defends his kingdom from the Greyjoys, Jon confronts an escalating threat, and Daenerys and her dragon allies continue to grow in power.
Reprint. Originally published: c2000.
Keywords: Imaginary wars and battles -- Fiction; Magic -- Fiction; Supernatural -- fiction; Magic -- Fiction; Fantastic fiction; Fantasy fiction; Paranormal fiction